Zero and Minimal Fluoroscopic Approaches During Ablation of Supraventricular Tachycardias: A Systematic Review and Meta-Analysis - Debreceni, Dorottya; Janosi, Kristof; Vamos, Mate; Komocsi, Andras; Simor, Tamas; Kupo, Peter (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Catheter ablations for cardiac arrhythmias are conventionally performed under fluoroscopic guidance. To guide these procedures, zero/minimal fluoroscopy (Z/MF) approaches have become available, using three dimensional electroanatomical mapping systems. Our aim was to conduct a meta-analysis comparing these two different methods for the treatment of paroxysmal supraventricular tachycardias (SVT). Methods: Electronic databases were searched and systematically reviewed for studies comparing procedural parameters and outcomes of conventional, fluoroscopy-guided vs. Z/MF approaches in patients undergoing EP procedures for SVTs. The random-effects model was used to derive mean difference (MD) and risk ratios (RR) with 95% confidence interval (CI). Results: Twenty-four studies involving 9,074 patients met our inclusion criteria. There was no difference between the groups in terms of acute success (RR=1.00, 95% CI, 0.99–1.01; p=0.97) and long-term success rate (RR:1.01, 95% CI, 1.00–1.03; p=0.13). Compared to the conventional method, Z/MF ablation significantly reduced fluoroscopic (MD: - 1.58 min (95% CI, -2.21 to -0.96 min; p<0.01)) and ablation time (MD: -25.23 s (95% CI: -42.04 to -8.43 s; p<0.01)). No difference could be detected between the two groups in terms of the procedure time (MD: 3.06 min (95% CI: -0.97 to 7.08; p=0.14)) and the number of ablation applications (MD: 0.13 (95% CI: -0.86 to 1.11; p=0.80)). Complication rate was 1.59% in the entire study population and did not differ among the groups (RR: 0.68, 95% CI: 0.45–1.05; p=0.08). Conclusions: The Z/MF approach for the catheter ablation of SVTs is a feasible method that reduces radiation exposure and ablation time without compromising the acute and long-term success, or complication rates. Key words: zero fluoroscopic, meta-analysis, paroxysmal supraventricular tachycardia, catheter ablation